Cystic Echinococcosis: Clinical, Immunological, and Biomolecular Evaluation of Patients from Sardinia (Italy) - Cinzia Santucciu; Piero Bonelli; Angela Peruzzu; Alessandro Fancellu; Vincenzo Marras; Antonello Carta; Scilla Mastrandrea; Giorgio Bagella; Toni Piseddu; Stefano Profili; Alberto Porcu; Giovanna Masala (Pathogens, 2020)
Cystic echinococcosis (CE), a zoonotic disease caused by the larval stage of the tapeworm Echinococcus granulosus sensu lato (s.l.), is a worldwide public health problem. Echinococcus granulosus sensu stricto (s.s.), associated with G1 and G3 genotypes, is endemic with high prevalence in the Mediterranean basin. The parasite’s life cycle comprises definitive hosts (canids) and intermediate hosts (ruminants) and can occasionally involve humans. The main aim of this research was to confirm the diagnosis of 13 patients suspected of CE who presented different complications and needed the surgical removal of the cysts. We also wanted to understand and clarify more the diagnosis of echinococcosis in humans. For this purpose, the patients first underwent cyst evaluation by ultrasound (US), immunological analysis, and then total pericystectomy, followed by parasitological, histopathological, and molecular biology examinations of the cysts. US stadiated one CE1, one CE2, eight CE3b, one CE4, and two CE5; immunology evidenced nine positives; histopathology confirmed 11 CE cysts, of which 8 fertile presenting protoscoleces were identified as E. granulosus s.s. by molecular biology, genotyped as three G1 and four G3 by neighbor-joining (NJ) phylogenetic tree. In conclusion, the results showed that 11 patients were affected by E. granulosus s.s. G1 orG3, and 2 cystic neoformations were of non-parasitic origin.